The Optimal Performance of the Energy Efficiency of a Pulse Dust Collection System towards Sustainability - Chun-Ling Ho (MDPI AG, 2021)
A growing number of manufacturers are realizing cost and environmental benefits through the sustainability of innovation and optimization processes. Based on polluting less and creating less, the study is pursuing sustainability on increasing operational efficiency by reducing costs and waste. Pulse dust collection systems are commonly used filtration equipment in industries and have lots of energy consumption due to running all day. This study is focused on the optimal parameters for energy saving and cost reduction, and the model is represented by the pressure drop of the filter and the residual powder. The characteristic values of the cleaning efficiency and the air permeability reduction are used for MATLAB to analyze the optimization state. This study found that the material of filter elements, the type of dust, the conditions of pulse-jet, and the filtering speed are the factors that affect the operational efficiency. In terms of cost, the pulse interval time in 10 s is the best parameter, and the pulse time does not affect the overall cost of the filter. Considering energy saving, 0.1 s of the pulse time is the best parameter. In addition, a lower dust concentration is a way to improve efficiency for increasing the filter life and reducing cost.